Analisis Penerimaan Pengguna Aplikasi Mobile UC Browser Menggunakan Model Unified Theory of Acceptance and Use of Technology (UTAUT) dan Task Technology Fit (TTF) - Atiyyah Lia Hijriyati; Niken Hendrakusma Wardani; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
UC Browser as a service provider of mobile browser has a market share of 28.51% in the domestic market that drove it into the most popular mobile browser. Many groups have done review and testing of the UC Browser showed mixed results. Some user complained about several problems in UC Browser. This impacts on the decrease of UC Browser monthly page view in 2016. Therefore it is necessary to do research on the acceptance of users to find out what factors affect the usage of UC Browser. This research combine Task Technology Fit (TTF) and Unified Theory of Acceptance and Use of Technology (UTAUT) with construct Attitude in order to know the user acceptance of the UC Browser. Data collection was done using online questionnaires. The collected data was then analyzed using Partial Least Square (PLS). The results show that behavior intention along with task technology fit have positive effect on use behavior. The research model can only explain 54.9% of the variance in the formation of UC Browser usage behavior. Therefore, it is necessary to develop the research model so that the prediction accuracy of the model variants increased.